STRATEGIC MANAGEMENT PRACTICES AND PERFORMANCE OF MANDERA COUNTY GOVERNMENT, KENYA - Ali, Abubakar Mohamed; Wambua, Dr. Philip (European Journal of Business and Strategic Management, 2019)
Purpose: The purpose of this study was to determine the effect of Strategic Management practices on Performance of Mandera County Government, Kenya Methodology: This study adopted a descriptive survey design. The target population was 70 employees of Mandera County Government comprising of top, middle and lower level county management staff i.e. It consisted of 14 Top level Management (County Executive Committee members and Chief Officers) 21 Middle Level Management (Directors) & 35 Lower Level Management (Assistant Directors and supervisors) who deal directly with the day-to-day operations. Data was collected using close ended questioners and analyzed & summarized using SPSS. Data analysis included both descriptive and inferential analysis where by descriptive statistics compared variables numerically and make interpretation easier, results were presented in graphs and tables and inferential analysis employed both correlation and regression analysis. Findings: Adoption of technology has led to the development of new services, functions & formation of new alliances with other Organization, Various departments coordinate and share information with each other and their coordination affected performance also Mandera County Government acquires knowledge from external sources for developing new ideas, knowledge is shared across units and successfully integrates existing knowledge with new information and knowledge acquired In addition Management have the ability to coordinate, expertise to design jobs to suit staff capabilities and interest, attract and retain creative employees, allocate resources, forecast and plan to achieve results however the county was not able to use technology efficiently to provide more service to its citizens and was not able to lead and maintain technological change in the county. Unique contribution to Theory, Practice and Policy: it was recommends that monitoring and adapting to technological changes should be given higher priority and promoting technological innovations among the county employees in order to gain competitive advantage and superior organizational performance, Managers should give employees job descriptions with clear performance indicators and delegate adequate authority also County Mandera Government should implement the knowledge sharing practices to facilitate identification and management of relevant knowledge for smooth operation of the institution